Identification of prognostic factors in pancreatic cancer - Ruiz-Tovar Polo, Jaime; Martín Pérez, E.; Fernández Contreras, María Encarnación; Reguero Callejas, M.E.; Gamallo Amat, C. (My University, 2011)
Background: Surgical resection is the only potentially curative treatment for pancreatic cancer, but it is associated with high complication rates. Outcome is poor, even in those resected cases. Identification of prognostic factors preoperatively may help to improve treatment of these patients, based on the expected response. Methods: A retrospective study of clinical variables of 59 patients with histological diagnosis of pancreatic carcinoma at University Hospitals Ramon y Cajal and La Princesa (Madrid, Spain) between 1999 and 2003 was performed. Results: We analyzed 59 patients (32 males and 27 females) with a mean age of 63.76 years. All patients were operated on, performing palliative surgery in 32% and tumor resection in 68%, including pancreaticoduodenectomy in 51% and distal pancreatectomy in 17%. Median overall survival was 14 months (range: 1-110 months). We observed that the presence of abdominal pain (p = 0.042) and back pain (p = 0.004) at diagnosis, palpation of abdominal mass at physical examination (p = 0.012), preoperative levels of hemoglobin <12 g/dl (p = 0.0006) and serum albumin <2.8 g/dl (p = 0.021), perineural infiltration (p = 0.025), lymph node affection (p = 0.004), stages II, III, and IV (p = 0.001), and presence of residual tumor (R+) (p = 0.008) are all associated with poor survival. Conclusions: Abdominal and back pain, palpation of abdominal mass at physical examination, preoperative levels of hemoglobin <12 g/dl and serum albumin <2.8 g/dl, perineural infiltration, lymph node affection, stages II, III, and IV, and the presence of residual tumor are associated with poor outcome.